Letter from Joseph E. Hoven to James Curtis Booth, September 3, 1866 - Hoven, Joseph E. (1866)
An application for the position of United States Mint Chief Coiner.
Keywords: Booth, James Curtis, 1810-1888; Mint of the United States; United States Mint; Hoven, Joseph E.